Effectiveness of Collaborative Learning in Improving Elementary Students' Indonesian Speaking Skills - Ambarsari, Juwita; Aprima, Desy (Journal of Innovation and Research in Primary Education, 2025)
Speaking skills constitute a fundamental component of language education, yet elementary students frequently encounter difficulties in oral communication development. Traditional teacher-centered approaches often limit opportunities for meaningful speaking practice, necessitating innovative pedagogical strategies. This study investigated the effectiveness of collaborative learning models on fourth-grade students' speaking skills in Indonesian language education. A quantitative pre-experimental design with one-group pretest-posttest configuration was employed at SD Negeri 01 Trans Bangsa Negara. Twelve fourth-grade students participated as research subjects using total sampling technique. Speaking competencies were assessed across multiple dimensions including pronunciation accuracy, intonation clarity, vocabulary appropriateness, eye contact maintenance, and speaking confidence using a validated instrument scored on a 100-point scale. The collaborative learning intervention involved small-group discussions, peer-supported text analysis, and collective retelling activities. Data analysis employed descriptive statistics and the Wilcoxon Signed-Rank Test due to non-normal data distribution. Students demonstrated substantial improvement in speaking performance following the collaborative learning intervention. Mean scores increased significantly from 37.1 (pretest) to 76.0 (posttest), representing more than a doubling of initial performance levels. The Wilcoxon Signed-Rank Test revealed statistically significant differences between pretest and posttest measurements (Z = -3.072, p = 0.002), indicating that most students progressed from below-standard performance to meeting or exceeding proficiency requirements. The findings provide empirical validation that collaborative learning models effectively enhance speaking skills by creating supportive environments that reduce communication anxiety while promoting active peer interaction. Results align with previous research demonstrating collaborative learning's capacity to foster positive emotional conditions and authentic communication opportunities essential for oral skill development. The study contributes practical evidence supporting the integration of collaborative approaches in Indonesian language curricula to address persistent challenges in speaking competency development at the elementary level.